Comparative study of 0.5% hyperbaric bupivacaine with sufentanil (5µg) and 0.5% hyperbaric bupivacaine for spinal anesthesia - Hakkim, Abdul; Kirubahar, Rajaclimax; Kanna, Vijay; Kanagasabai, Murugadoss (International Journal of Research in Medical Sciences, 2017)
Background: In the present day practice of Anesthesiology, bupivacaine is the most commonly used drug for spinal anesthesia. To improve the quality of analgesia and prolong the duration of its action, many adjuvants have been tried. Intrathecal opioids have been found to fulfil both these objectives. This study was done to evaluate the effects of adding sufentanil to bupivacaine for spinal anesthesia. Methods: 100 ASA grade I/II patients aged between 20 – 60 years undergoing elective lower abdominal, urologic, lower limb surgeries were selected and divided into two groups of 50 each. Group A received 2.5 ml of heavy Bupivacaine, whereas the second group B received 2.5 ml of heavy Bupivacaine with 5 µg Sufentanil. Parameters - Onset and duration of sensory block and motor block, time for two dermatomal segments regression, duration of analgesia, vitals and side effects were assessed. Results: There was no variation in onset of sensory blockade and motor blockade. The time to achieve peak sensory level was 3 minutes earlier in group B. The time for two segment regression and the time to full sensory and motor recovery were prolonged in Group B. Duration of complete and effective analgesia prolonged by 40-60 minutes and the time for first request of analgesic postoperatively was delayed by 70 - 80 minutes in group B. The quality of analgesia was better in group B. Pruritus was the common side effect in group B. Conclusions: Sufentanil potentiates bupivacaine spinal anesthesia by increasing the duration and improving the quality of analgesia with minimal side effects.